Gay men's experiences of surrogacy clinics in India. Issue 1 (28th October 2014) - Riggs, Damien W; Due, Clemence; Power, Jennifer
Abstract : While growing numbers of Australian gay men are entering into 'offshore' surrogacy arrangements in order to become parents, little empirical research has been conducted with this population. This article reports on a qualitative analysis of interviews with 12 gay men who had entered into surrogacy arrangements in India. The findings outline both positive and negative experiences in terms of support pre-conception, during the birth and post-birth. Changes to legislation in India mean that gay men can no longer access surrogacy services there, but it is important to understand the experiences of men who had previously accessed those services. The article concludes by highlighting aspects of the data that demonstrate the particular experiences of gay men who undertake offshore surrogacy arrangements, especially with regard to their need for support and involvement in all aspects of the process. A more thoroughly developed network of care may help to facilitate such support and this may further increase the positive outcomes reported by gay men who form families through surrogacy arrangements.